مستوى الأداء التدريسي للأستاذ الجامعي في ظل نظام Lmd وعلاقته بإتجاهات الطلبة نحو مهنة التدريس (من وجهة نظر طلبة علوم وتقنيات الأنشطة البدنية والرياضية المقبلين على التخرج بورقلة). - حبيب, علي; نجيب, عبابسة; بركات, حسين (جامعة الوادي - University of Eloued, 2022)
دفت الدرسة للتعرف على مستوى ممارسة الأستاذ الجامعي لمهارات التدريس من وجهة نظر الطلبة المقبلين على التخرج و علاقتها بإتجاهاتهم نحو مهنة التدريس في ظل نظام أل ام دي ، و أتبع الباحثون المنهج الوصفي، وأستخدم الباحث إستبيان لقياس جودة مهارات التدريس من وجهة نظر الطلبة و مقياس جاهز لقياس الإتجاهات نحو مهنة التدريس ، وقدرت عينة البحث ب(70) طالبا، وتوصلت النتائج لوجود علاقة متوسطة بين مستوى ممارسة الاستاذ الجامعي لمهارات التدريس من وجهة نظر الطلبة وإتجاهاتهم نحو مهنة التدريس . الكلمات المفتاح : الأداء التدريسي؛ الأستاذ الجامعي ؛ نظام LMD ؛ الإتجاه نحو مهنة التدريس ؛ الطلبة المقبلين على التخرج. Abstract: The study aimed to identify level of teaching skills wichich the professor practice from the perspective of students and their relationship orientation to attitudes toward the teaching professio under lmd system, researchers followed the descriptive approach, the researchers used questionnaire to measure of level of teaching skills from the students point of view and measure of the attitudes toward the teaching profession ,the sample study was estimated at (70 students ). ،the results found that there is moderate relationship between level of teaching skills wichich the professor from the perspective of students to attitudes toward the teaching profession.
level of teaching performance at universty professor under LMD system and its relationship orientation to attitudes toward the teaching profession(from the point of view ofstudents of science and techniques of physical and sports activities coming to graduate
مقال
Keywords: الأداء التدريسي ، الأستاذ الجامعي ، نظام ، الإتجاه نحو مهنة التدريس، الطلبة المقبلين على التخرج; the teaching profession, universty professor, LMD system, attitudes toward the teaching profession , students coming to graduate.